2013
DOI: 10.3727/096368912x654948
|View full text |Cite
|
Sign up to set email alerts
|

ZNF281 Knockdown Induced Osteogenic Differentiation of Human Multipotent Stem Cells in Vivo and in Vitro

Abstract: ZNF281 is one of the core transcription factors in embryonic stem cells (ESCs) and has activation and repression roles in the transcription of ESC genes. A known target molecule of Zfp281 (the mouse homologue of ZNF281) is Nanog. However, NANOG is not expressed in most human multipotent stem cells (hMSCs). Here, we investigated the roles of ZNF281 with a gain- and loss-of-function study. The knockdown of ZNF281 in vivo and in vitro resulted in spontaneous osteochondrogenic differentiation and reduced the proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 50 publications
2
18
0
Order By: Relevance
“…However, ZNF281 may also promote β‐catenin/TCF4 activity by mediating the loss of E‐cadherin expression, which is known to inhibit nuclear localization and activity of β‐catenin by recruiting it to the cell membrane (Sadot et al, 1998; Orsulic et al, 1999). Furthermore, our results are consistent with the reported correlation of ZNF281 and β‐catenin expression in hMSCs (Seo et al, 2013). We found that ZNF281 induces expression of the prognostic stem‐cell markers CD133 and LGR5.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, ZNF281 may also promote β‐catenin/TCF4 activity by mediating the loss of E‐cadherin expression, which is known to inhibit nuclear localization and activity of β‐catenin by recruiting it to the cell membrane (Sadot et al, 1998; Orsulic et al, 1999). Furthermore, our results are consistent with the reported correlation of ZNF281 and β‐catenin expression in hMSCs (Seo et al, 2013). We found that ZNF281 induces expression of the prognostic stem‐cell markers CD133 and LGR5.…”
Section: Discussionsupporting
confidence: 93%
“…The enhancement of β‐catenin activity by ZNF281 may contribute to ZNF281‐induced stemness, since WNT signalling is necessary to maintain stem cells in the intestinal crypts (Pinto and Clevers, 2005; Brabletz et al, 2005b; Scoville et al, 2008). Interestingly, ZNF281 directly binds to the β ‐catenin promoter in human multipotent stem cells (hMSCs) (Seo et al, 2013). In addition, we found that ZNF281 directly represses Axin2 , a negative regulator of the WNT pathway (Lustig et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, quantitative ChIP analysis revealed that ZBP-99 occupies the promoter of the Wnt target gene LGR5 , which ultimately increases β-catenin activity and the acquisition of stem cell traits (38). ZBP-99 binds the proximal CTNNB1 promoter and induces CTNNB1 mRNA in osteogenic stem cells, demonstrating that a ZBP-89 family member directly binds and regulates CTNNB1 gene expression (40). Thus, ZBP-99, a ZBP-89 family member, is able to indirectly regulate β-catenin activity in CRC cell lines, and directly bind to the CTNNB1 promoter in specific cell types, suggesting that ZBP-89 might also regulate CTNNB1 gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…We used miRanda (19), PicTar (20), and TargetScan (21) to predict the targets of miR-188. Among the predicted genes, we chose 6 for further analysis-histone deacetylase 9 (Hdac9), RPTORindependent companion of MTOR complex 2 (Rictor), phosphatase and tensin homolog (Pten), zinc finger protein 281 (Znf281), GLIS family zinc finger 3 (Glis3), and ephrin B2 (Efnb2)-which had been reported to participate in bone metabolism (22)(23)(24)(25)(26)(27)(28). Overexpression or inhibition of miR-188 changed endogenous levels of HDAC9 and RICTOR protein, but not the others ( Figure 8A).…”
Section: Aging Induces Mir-188 Expression In Bmscsmentioning
confidence: 99%